POLA SANKSI ADMINISTRATIF BAGI PERUSAHAAN PENYEDIA JASA TENAGA KERJA INDONESIA TERHADAP PERLINDUNGAN BURUH MIGRAN INDONESIA DI LUAR NEGERI - Tri Sulistiyono; Pratama Herry Herlambang; Masyita Isnadya Risky Salsabila (Universitas Negeri Semarang, 2020)
The same significant risk also overshadows the lure of high wages to be a migrant worker abroad. The number of workers moving from home to foreign countries is increasing. The high risk and high interest cause migrant workers to be vulnerable to being deprived of their rights; therefore, they need to be protected by the state. This study seeks to examine the application of the pattern of sanctions obtained by companies providing labor services as migrant workers and protection for Indonesian migrant workers. The research was conducted using an empirical juridical approach where the reality that occurred in the field was studied and compared with the applicable legal provisions. The aim is to find out the legal protections for migrant workers and the sanctions for Indonesian Manpower Service Providers.